(untitled) (Tikrit Journal of Pharmaceutical Sciences, 2023)
There are different methods for identification bacteria,we used culture methods,biochemical tests and molecular method,the aim of this study to decide the measure of efficient select gene for the recognition of the S. pneumonia by molecular tests -specific polymerase chain reaction(PCR),the assay targeting lytA gene from keratitis and conjunctivitis in patients and clients wearing contact lenses in several centers in Erbil city, the results showed that out of 12 investigated S.pneumoniae isolates by culture methods and biochemical testes ,lytA gene is found in 6(50%).all 6 of the positive lytA isolates encapsulated ,Norfloxacin and Seftazidime were the best antibiotics (100% ,83.3%) respectively, most infections was keratitis(cornal infections),in addition the majority of patients and clients were among females 78(60%),32(24.6)of patients and clients in the average age ranging from(15-20)years ,80(61.5%) of infections recoded of those who are putting cosmetic lens